2020
DOI: 10.3390/ijerph17020573
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Knee Muscle Strength and Fat/Muscle Mass in Elderly Women with Knee Osteoarthritis Based on Dual-Energy X-Ray Absorptiometry

Abstract: Purpose: This study aimed to examine the characteristics and correlation of knee muscle strength and body composition (fat and muscle mass) among elderly women aged 60–70 years with knee osteoarthritis. The present study hypothesized that the muscle mass and the peak torques of the knee joints were considerably low in the knee osteoarthritis (KOA) group. Methods: A total of 47 elderly women aged 60–70 years were recruited from Yangpu District in Shanghai and assigned to the knee osteoarthritis (n = 25, KOA) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 45 publications
4
19
0
1
Order By: Relevance
“…OA commonly affects knee and hip joints, and it impairs muscle morphology and function, leading to physical disability [3][4][5], especially in individuals with obesity [6,7]. Observational studies have indicated that older individuals with OA exhibited lower muscle mass or volume than healthy controls [3,5,8,9], and having less muscle was further associated with lower muscle strength and poor functional outcomes [10,11]. Recent studies have reported that OA was associated with high risk of sarcopenia [12,13], an age-related condition characterized by attenuated muscle mass [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…OA commonly affects knee and hip joints, and it impairs muscle morphology and function, leading to physical disability [3][4][5], especially in individuals with obesity [6,7]. Observational studies have indicated that older individuals with OA exhibited lower muscle mass or volume than healthy controls [3,5,8,9], and having less muscle was further associated with lower muscle strength and poor functional outcomes [10,11]. Recent studies have reported that OA was associated with high risk of sarcopenia [12,13], an age-related condition characterized by attenuated muscle mass [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This translates into an increased risk of poor quality of life, physical disability, frequent falls and weakness, and death. In this sense, four manuscripts [ 3 , 8 , 9 , 11 ] in this special issue, corresponding to 33.3% of the total, corroborate that muscle loss is the typical consequence of all older adults. The study by Patiño-Villada et al [ 8 ] considers the combination of high muscle mass and shallow fat mass a highly healthy variety.…”
mentioning
confidence: 58%
“…This special edition of the Journal of Environmental Research and Public Health ( IJERPH ) has brought together eleven research manuscripts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ] and a brief report [ 12 ]. This special issue, entitled “ Sarcopenia, Exercise and Quality of Life ” gathered 12 manuscripts [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]; four (33.3%) manuscripts are related to the impact of physical activity concerning sarcopenia [ 4 , 6 , 7 , 10 ]. Two manuscripts were used for the Wii Fit ® games as an intervention tool for physical activity in institutionalized elderly patients [ 4 , 6 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations